A Companion to Alfred Hitchcock - Leitch, Thomas M.; Poague, Leland A. 1948- (Wiley-Blackwell companions to film directors, 2011)
"Alfred Hitchcock remains the quintessential cinematic auteur - the director as hero. Fifty years of debate over his status as an obsessive and dictatorial artist has raised increasingly pressing questions about the relation between individual authorship, on the one hand, and contexts, influences, and collaborators, on the other. A Companion to Alfred Hitchcock authoritatively maps the body of work generated in response to the director and his films, compiling essays from some of the world's most noted scholars in the emerging field of Hitchcock studies"--